A Financial Instrument - Derivatives (Trinity Journal of Management, IT & Media (TJMITM), 2010)
A financial co111ract that derives its  rnlue from another asset or an index  of asset values is k11ow11 as  derivative. These underlying assets  may be Foreign Exchange, Bonds,  Equities or Commodities. For  example, Forward Contracts relate  to Foreign Exchange; Future to  Commodities, Debt Instruments,  currencies or Stock Indices; and  Option to Equities. Derivatives are traded at organized  exchanges and in the Over-the Counter (OTC) market.Derivatives  traded at exchanges are  standardized contracts having  standard delivery dates and trading  units. OTC derivatives are  customized contracts that enable the  parties to select the trading units and  delivery dates to suit their  requirements. Moreover, there are  fewer regulatory restrictions and this  facilitates innovation. A major  difference between the two is that  counterparty risk - the risk of default  by either party; With exchange  traded derivatives, the risk is  controlled by exchanges through  clearing houses which act as a  contractual intermediary and impose  margin requirements. In contrast,  OTC derivatives signify greater  vulnerability. Options derive their  values from shares or stock market  indices; an option confers the right  without any obligation to buy or sell  an asset at a predetermined price on  or before a stipulated expiration  date. Interest -rate futures are tied  to debt instruments. It is a financial contract that derives its value from another asset or an index of  asset values. A derivative has no physical existence but emerges out of a  contract between two parties. It does not have any value of its own but its  value, in tum, depends on the value of other physical assets which are called  underlying assets. These underlying assets may be foreign exchange, bonds,  equities or commodities. Derivatives can be thought of on the price of  something. Suppose you bet with your friend on the price of a bushel of com. If  the price in one year is less than $3 your friend pays you $1. If the price is more  than $3 you pay your friend $1. Thus, the underlying in the agreement is the  price of com and the value of the agreement to you depends on that underlying.
Keywords: Derivatives; Foreign Exchange; Bonds; OTC